Prognostic impact of lymph node metastasis in distal cholangiocarcinoma. Issue 4 (22nd January 2015) - ,; Shimoyama, Y; Fukami, Y; Miyake, H; Sakamoto, E; Takara, D; Shirai, K; Ohira, S; Tojima, Y; Hashimoto, M; Akutagawa, A; Yamaguchi, R; et al.
Abstract: Background: The aim of the study was to investigate the prognostic impact of lymph node metastasis in cholangiocarcinoma using three different classifications. Methods: Patients who underwent pancreaticoduodenectomy for distal cholangiocarcinoma in 24 hospitals in Japan between 2001 and 2010 were included. Survival was calculated by means of the Kaplan–Meier method and differences between subgroups were assessed with the log rank test. The Cox proportional hazards model was used to identify independent predictors of survival. χ 2 scores were calculated to determine the cut-off value of the number of involved nodes, lymph node ratio (LNR) and total lymph node count (TLNC) for discriminating survival. Results: Some 370 patients were included. The median (range) TLNC was 19 (3–59). Nodal metastasis occurred in 157 patients (42·4 per cent); the median (range) number of involved nodes and LNR were 2 (1–19) and 0·11 (0·02–0·80) respectively. Four or more involved nodes was associated with a significantly shorter median survival (1·3 versus 2·2 years; P = 0·001), as was a LNR of at least 0·17 (1·4 versus 2·3 years; P = 0·002). Involvement of nodes along the common hepatic artery, present in 21 patients (13·4 per cent), was also associated with a shorter survival (median 1·3 versus 2·1 years; P = 0·046). Multivariable analysis among 157 node-positive patients identified the number of involved nodes as an independent prognostic factor (risk ratio 1·87; P = 0·002). Conclusion: The number of involved nodes was a strong predictor of survival in patients with distal cholangiocarcinoma. Abstract : Number of involved nodes predicts survival after surgery